Proven Delivery Models for LED Public Lighting : Municipal Financing Delivery Model in Quezon City, Philippines - Makumbe, Pedzisayi (World Bank, Washington, DC, 2016)
This paper entitled with Municipal Financing Delivery Model in Quezon City,Philippines, is one in a series of seven knowledge products produced by ESMAP in an attempt to help cities work through the challenges associated with implementing LED public lighting programs. The publications include six case studies and a synthesis report which summarizes the case studies. Each case study describes the context in which decisions were made, then recounts the problems encountered andsolved to realize the implementation of the programs. The challenges include real-life examples of: cities managing to attract private sector participants toprovide necessary financing and technical expertise; programs implemented in municipalities that are not credit worthy and have limited policy and institutional support; small municipalities of about 2,500 residents as well as cities with several million residents; cities managing perceived risks; and cities effectively handling the measurement and verification of electricity savings accruing from the implementation of more efficient LEDs.